Life and Mortality in Ugaritic : A Lexical and Literary Study - McAffee, Matthew (Book collections on Project MUSE., 2019)
"Identifies and analyzes the Ugaritic terms most commonly used to talk about life and mortality in order to construct a more representative framework of the ancient perspective on these topics"--Provided by publisher.